Induction of ischemic stroke in awake freely moving mice reveals that isoflurane anesthesia can mask the benefits of a neuroprotection therapy - Seto, Angela; Friesen, Stephanie; Trudeau, Dustin; Swan, Ian; Leung, Jay; Reeson, Patrick; Delaney, Kerry; Brown, Craig E. (Frontiers in Neuroenergetics, 2014)
Anesthetics such as isoflurane are commonly used to sedate experimental animals during the induction of stroke. Since these agents are known to modulate synaptic excitability, inflammation and blood flow, they could hinder the development and discovery of new neuroprotection therapies. To address this issue, we developed a protocol for inducing photothrombotic occlusion of cerebral vessels in fully conscious mice and tested two potential neuroprotectant drugs (a GluN2B or α4β2 nicotinic receptor antagonist). Our data show in vehicle treated mice that just 20 minutes of exposure to isoflurane during stroke induction can significantly reduce ischemic cortical damage relative to mice that were awake during stroke. When comparing potential stroke therapies, none provided any level of neuroprotection if the stroke was induced with anesthesia. However, if mice were fully conscious during stroke, the α4β2 nicotinic receptor antagonist reduced ischemic damage by 23% relative to vehicle treated controls, whereas the GluN2B antagonist had no significant effect. These results suggest that isoflurane anesthesia can occlude the benefits of certain stroke treatments and warrant caution when using anesthetics for pre-clinical testing of neuroprotective agents.